IDENTIFIKASI KELENGKAPAN SARANA DAN PRASARANA DI DAYA TARIK WISATA JOPURO BANYUWANGI - Febrian, Ayu Wanda; Arahma, Annisa (Jurnal Kajian dan Terapan Pariwisata, 2024)
Jopuro Banyuwangi tourist attraction is a natural tourist attraction that offers natural beauty, such as springs, rivers and rice fields. However, based on identification, the completeness of facilities and infrastructure in Jopuro is still minimal. The minimal completeness of facilities and infrastructure at a tourist attraction will affect the standardization of the facilities provided when visiting Jopuro tourist attraction. The method used is a descriptive qualitative method. This method was used to identify the completeness of facilities and infrastructure in Jopuro tourist attraction. Data collection techniques were carried out by conducting direct observations in the field, interviews with managers, literature studies and documentation of existing facilities and infrastructure. Based on the research results, the facilities and infrastructure at Jopuro tourist attraction are quite complete but need to be improved in quality to provide comfort for tourists. Data also shows that the number of visits to Jopuro tourist attraction continues to increase every year. This is influenced by the main attraction of this destination which offers bathing activities with a natural concept, a network of relationships with TV media, as well as the location of Rejopuro hamlet as a transit for foreign tourists who will climb the Ijen Crater TWA. The advice that the author can give in this research is that Jopuro tourist attraction needs to improve the quality of managers or human resources (HR) in maintaining and developing tourism facilities and infrastructure.